2007
DOI: 10.5897/ajb2007.000-2421
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological safety of gari, lafun and ogiri in Akure metropolis, Nigeria

Abstract: The microbiological safety of three locally fermented foods (gari, lafun and ogiri) was investigated in this work. Ten different samples each of the fermented foods were collected at the central market (Oja Oba). The mean total bacterial count in the samples of gari, lafun and ogiri were 14.3 x 10 4 , 13.2 x 10 5 and10.2 x10 6 cfu/g, respectively. Also the mean total viable count of mould was 1.6 x 10 4 , 3.7 x 10 5 and 8.2 x 10 6 cfs/g, respectively. Bacteria isolated from gari include Corynebacterium species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…Meanwhile, sample MNI was found to have the highest amount of aerobic bacterial count of 4.8 × 10 6 cfu/g, while sample EOS had the highest count of 5.3 × 10 6 cfu/g among the samples from the markets. These values were higher than the findings of microbial count of the fermented flour obtained by [ 20 ] who reported 1.5 × 10 6 cfu/g. It was also higher than the findings of [ 17 ] who reported 2.7 × 10 3 to 1.2 × 10 7 cfu/g.…”
Section: Resultscontrasting
confidence: 75%
“…Meanwhile, sample MNI was found to have the highest amount of aerobic bacterial count of 4.8 × 10 6 cfu/g, while sample EOS had the highest count of 5.3 × 10 6 cfu/g among the samples from the markets. These values were higher than the findings of microbial count of the fermented flour obtained by [ 20 ] who reported 1.5 × 10 6 cfu/g. It was also higher than the findings of [ 17 ] who reported 2.7 × 10 3 to 1.2 × 10 7 cfu/g.…”
Section: Resultscontrasting
confidence: 75%
“…Microbiological safety Ijabadeniyi, 2007;Nwabueze & Odunsi, 2007 Increased shelf life and reduced bulkiness through drying Oyewole & Phillip, 2004 White colour and improved texture, increased palatability Uzogara et al, 1990;Oyewole & Afolami, 2001;Sanni et al, 2003 Cyanogens reduction…”
Section: Leuconostoc Sppmentioning
confidence: 98%
“…Protein enrichment Fagbemi & Ijah, 2006;Akindahunsi & Oboh, 1999 Reduction of offensive odour and improved palatability, texture and shelf-life Iwuoha & Eke,1996;Tomlins et al, 2007;Akingbala et al, 2006;Okoro, 2007 Cyanogens reduction Ijabadeniyi, 2007;Nwabueze & Odunsi, 2007 Increased shelf life and reduced bulkiness through drying Oyewole & Phillip, 2004 White colour and improved texture, increased palatability Uzogara et al, 1990;Oyewole & Afolami, 2001;Sanni et al, 2003 Cyanogens reduction…”
Section: Leuconostoc Sppmentioning
confidence: 99%
“…The mean total aerobic plate count obtained from most garri samples in this study was 5.42 log cfu/g, which exceeds the recommended maximum acceptable limit (3.0 log cfu/g) for dried food products [4]. However, Ijabadeniyi [21] reported low count of microorganisms in garri at Akure metropolis, Nigeria and concluded that such low count is not enough to establish any health risk.…”
Section: Discussionmentioning
confidence: 50%